Multigram preparation of tungsten microfibers via needle-less electrospinning of phosphotungstic acid. (April 2023) - Kundrat, Vojtech; Vykoukal, Vit; Moravec, Zdenek; Kral, Zdenek; Machac, Petr; Simonikova, Lucie; Pinkas, Jiri
Abstract: Metallic tungsten microfibers were prepared in a multigram yield by electrospinning from the aqueous phosphotungstic acid/polyvinyl alcohol (PVA) solution in three steps. Green composite microfibers of H3 PW12 O40 /PVA were easily electrospun from precursor solutions on a Nanospider instrument with a cylindrical rotating electrode. Subsequent oxidation of the organic PVA matrix and decomposition of phosphotungstic acid in the air at 600 °C provided ceramic WO3 /P2 O5 fibers. Finally, prepared oxide fibers were reduced in a forming gas atmosphere at temperatures up to 1000 °C. During the reduction, all phosphorus was removed, and pure metallic tungsten microfibers were produced. Graphical abstract: Unlabelled Image Highlights: Polycrystalline tungsten fibers prepared by needleless electrospinning. An aqueous solution of phosphotungstic acid and PVA used as precursors. Green fibrous composite mat calcined in air at 600 °C to (WO3 )12 /(P2 O5 )0.5 fibers. Oxide fibers reduced in forming gas at 1000 °C to pure metallic W fibers.